The need to review the Malaysia’s education policy: a comparative study with the USA / Muhsin Izhar Hisham, Nurhidayah Kamsani and Nursyazwani Bahzin - Hisham, Muhsin Izhar; Kamsani, Nurhidayah; Bahzin, Nursyazwani (2011)
This research is basically a comparative legal study on education policy between Malaysia and the United States of America. This study sets out to discover the inadequacies of Malaysia's education policy as to the global needs today. Thus study also seeks to discover whether the American education policy is better than ours and the possibility of its application to the Malaysian current standing. There are negative perceptions on students who cannot excel academically and there is also poor mastery of English language as the second language. Evidences obtained through the research showed that it was due to several inadequacies in our education policy. We found that there are several American education policies that may be suitable to be incorporated in our education policy. But still, such incorporation should be slightly amended so it would suit with the uniqueness of Malaysian culture and society.